Molecular microbiology in aquaculture: the search for a healthy microbial community - Duarte, Leticia Novaes (2018)
The microbial communities of aquaculture systems are involved in maintaining the health and growth of farmed organisms. They participate in nutrient cycling, nutrition, disease control and water quality of the system and effluents. We use DGGE fingerprint techniques and high-throughput sequencing analyzes to access the semi-intensive and intensive aquaculture microbiota. First, we investigated the composition of the bacterioplankton communities of a recirculating aquaculture system (RAS) used for the production of juveniles sole (Solea senegalensis). The most abundant orders detected in the aquaculture of sole were: Alteromonadales, Rhodobacterales, Oceanospirillales, Vibrionales and Flavobacteriales. OTUs related to potential fish pathogens in aquaculture systems were detected, as well as naturally occurring probiotic bacteria. These may have played a role in suppressing potential pathogens of fish, keeping the aquaculture free from disease. In an aquaculture of adult sole, the presence of fish was described as the main factor influencing bacterial composition. Here, supply water served as an important seed bank for the colonization of bacterial populations in the hatchery RAS tanks, mainly related to probiotic bacteria. The importance of this compartment for the maintenance of a healthy aquaculture and its importance in the development of strategies for microbial manipulation/management of aquaculture was reinforced. Subsequently, we describe the seasonal dynamics and potential interactions of bacterial and microeukaryotic plankton communities in a semi-intensive aquaculture for European sea bass (Dicentrarchus labrax) over a year. The most abundant bacterial classes were Gammaproteobacteria, Flavobacteriia and Alphaproteobacteria; while the microeukaryotic communities were dominated by the Ochrophyta, Chlorophyta and Ciliophora groups. Here, in addition to the potential effects of abiotic parameters on microbial plankton, there was a correlation between bacterial and microeukaryote populations which may be an indication of trophic and / or metabolic interdependence between these two domains. These studies allowed us to describe the normal microbiota of aquaculture systems, their ecological interactions and the impacts exerted by environmental factors in order to support the development of strategies for the maintenance of a productive and healthy environment.